If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -3x = 5x + -12 Reorder the terms: 12 + -3x = -12 + 5x Solving 12 + -3x = -12 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 12 + -3x + -5x = -12 + 5x + -5x Combine like terms: -3x + -5x = -8x 12 + -8x = -12 + 5x + -5x Combine like terms: 5x + -5x = 0 12 + -8x = -12 + 0 12 + -8x = -12 Add '-12' to each side of the equation. 12 + -12 + -8x = -12 + -12 Combine like terms: 12 + -12 = 0 0 + -8x = -12 + -12 -8x = -12 + -12 Combine like terms: -12 + -12 = -24 -8x = -24 Divide each side by '-8'. x = 3 Simplifying x = 3
| (9/10)-(1/3)=x | | 5.972*2.71828=389.40563584 | | 7x-8(x+1)-3=3(x+4)-4(x+1) | | 3x+7=9x+3 | | 3n-5=-21 | | 33.33333=4+-1 | | c=0.75y+50 | | x+26=2x+4 | | 2x+y=110 | | (Y-6)-(y+6)=7y | | Y=ln(e^7x) | | 4x-10=-60-10x | | 41-5x=14-8x | | x+(x*0.28)=100 | | 10+6x=-15+x | | 3x-9=x+27 | | Ln(x-3)= | | -(-1k+1)=-5(1-6k)+7k | | b+3=3 | | y-9=-17 | | 4.8x+38.3=10.9-8.9x | | 1/3x-5/6=1/9x | | sqrt(2x^2-5x-3)=x+1 | | 15x^2+3x= | | x+sqrt(25-x^2)=7 | | 5y*2y-3= | | x^2+sqrt(25-x^2)=7 | | 2(x+1)+3x+6=4 | | 15x-7=-2 | | t^2+4t+3=0 | | 28=2x+2 | | 3lnx^6-2lnx^2=14 |